PROSES PRODUKSI KOPI SANTEN DI SURABAYA BARAT - ONNY PURNAMAYUDHIA ONNY YUDHIA; Ampar Jaya Suwondo; Bachtiar Rahman Halik (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The Community Service Program is a program that aims to provide training and assistance for SME partners, both in production and business management. After the survey was carried out, the Community Service Implementation Team collaborated with SME Partners. Santen Coffee